2009
DOI: 10.1128/cvi.00465-08
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Detection of H5N1 Subtype Influenza Viruses by Antigen Capture Enzyme-Linked Immunosorbent Assay Using H5- and N1-Specific Monoclonal Antibodies

Abstract: Highly pathogenic avian influenza (HPAI) virus of the H5N1 subtype has caused devastating damage to poultry flocks and sporadic human H5N1 infections. There is concern that this virus subtype may gain transmissibility and become pandemic. Rapid diagnosis and surveillance for H5N1 subtype viruses are critical for the control of H5N1 infection. In this study, we report a robust antigen-capture enzyme-linked immunosorbent assay (AC-ELISA) based on H5-and N1-specific monoclonal antibodies (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 23 publications
0
26
0
Order By: Relevance
“…The results indicate that the magnetic nanobeads amplification based QCM immunosensor was more sensitive than ELISA for AI H5N1 detection (Ho et al, 2009). The estimated detection limit of the antigen capture enzyme-linked immunosorbent assay (AC-ELISA) using H5-and N1-specific monoclonal antibodies was 1-2 HA titers, which showed that the QCM immunosensor developed with polyclonal anti-H5 antibodies was comparable with the ELISA technology in terms of sensitivity for H5N1 detection even without nanobeads for signal amplification.…”
Section: Detection Of Pure Ai H5n1 Virusmentioning
confidence: 96%
See 1 more Smart Citation
“…The results indicate that the magnetic nanobeads amplification based QCM immunosensor was more sensitive than ELISA for AI H5N1 detection (Ho et al, 2009). The estimated detection limit of the antigen capture enzyme-linked immunosorbent assay (AC-ELISA) using H5-and N1-specific monoclonal antibodies was 1-2 HA titers, which showed that the QCM immunosensor developed with polyclonal anti-H5 antibodies was comparable with the ELISA technology in terms of sensitivity for H5N1 detection even without nanobeads for signal amplification.…”
Section: Detection Of Pure Ai H5n1 Virusmentioning
confidence: 96%
“…As an alternative, biosensors have been studied for the detection of AI H5N1 virus (Kukol et al, 2008;Pavlovic et al, 2008;Deng et al, 2009;Ho et al, 2009;Tam et al, 2009;Ting et al, 2009;Wang et al, 2009) for rapid and reliable testing of influenza with minimal sample handling and laboratory skill requirements (Amano and Cheng, 2005). Microgravimetric quartz crystal microbalance (QCM), owing to its simplicity and cost effectiveness, has been extensively investigated as a transducer for virus detection such as influenza A and B viruses (Owen et al, 2007;Hewa et al, 2009), dengue virus Chen et al, 2009a), airborne vaccinia viruses (Lee et al, 2008), flavivirus (Tai et al, 2006), bovine ephemeral fever virus , hybridization of hepatitis B virus (Yao et al, 2008), human rhinovirus (HRV) and the foot-and-mouth disease virus (FMDV) (Tai et al, ,2006Jenik et al, 2009), and other viruses (Abad et al, 1998;Eun et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…(2) Non-RBS globular domain moderately conserved epitopes, comprising ten potential sites (Cao et al 2012;Du et al 2009;Hu et al 2012;Li et al 2011;Oh et al 2010;Prabakaran et al 2009a;Rockman et al 2013). (3) RBS variable epitopes; comprising a total of twenty potential epitopes Ferreira et al 2010;Hanson et al 2006;Ho et al 2009;Hoffmann et al 2005;Kaverin et al 2002Kaverin et al , 2007Khurana et al 2009;Li et al 2009;Masalova et al 2011;Ohkura et al 2012;Prabakaran et al 2009aPrabakaran et al , b, 2010Prabhu et al 2009;Rudneva et al 2010;Sun et al 2009;Wang et al 2009;Yang et al 2007;Yoshida et al 2009). …”
Section: Antigenic Characteristics Defined By Epitope Mappingmentioning
confidence: 99%
“…Lastly, proof of concept can be seen as a feasible means to finance innovation: for example, through seed funding, ignition grants, or innovation grants (Gulbranson and Audretsch, 2008). In terms of the agri-food sector in particular, the use of proof of concept is exemplified in the development of clinical immunology (e.g., vaccines for livestock, Ho et al, 2009), biotechnology (e.g., testing veterinary drug residues in food, Connolly et al, 2007), information management technology (e.g., Verloop et al, 2009), etc.…”
Section: Moneymentioning
confidence: 99%